mRNA extraction, cDNA synthesis and tillering specific gene isolation from BLB resistant Binashail rice - Jahan, Papia; Hossain, Ahmed; Nasiruddin, KM; Yasmin, Sabina; Khatun, Fahmida; Parvej, Md Shafiullah (Asian Journal of Medical and Biological Research, 2015)
Bacterial Leaf Blight (BLB) caused by Xanthomonas oryzaepv. oryzae (Xoo) bacteria, is a major biotic stress in the irrigated rice belts. Genetic modification is the most effective and economical control for bacterial blight disease. For high yielding, branching capacity is most important. Molecular survey was conducted to identify the presence of tillering specific gene in BLB resistant Binashail rice. Reproducible means of Binashail rice at 21 days was designed based on the timing of full expression of the leaf. PCR with primers specific for tillering specific gene was used in the study. The cDNA of Binashail rice synthesized by an improved RT-PCR technique, derived from the total mRNAs extracted from the plant leaf. Gel documentation showed that the size of the synthesized cDNA was 250bp and tillering specific gene was 201bp in length long. The identification of tillering specific gene in Binashal rice germplasm will help in accelerating the elite breeding program in future. Asian J. Med. Biol. Res. June 2015, 1(2): 265-270